METODE PENYAMBUNGAN PADA STRUKTUR BETON BERTULANG - Djoko Subari (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2003)
Â The magnitude of most concrete construction is such tahat interruption will inevitably accur to the placing of concrete. Whetherthe period of these interruptions be days, overnight, or merely 30 minutes, if it allows the concrete to stiffen to the extent that it cannot be worked, then a joint must be made. There will also be ocasions where for structural reasons it is considered necessary,to porposely break the continuity concrete placing and to construct a joint. Where construction joint to be made in structural member they should be located at a position where on either side of them can be nemed according in the type of movement they allow: contraction joint, dummy contraction or control joint, expansion joint, isolation joint. The positioning of joint and the type of joint may same time be governed be architectural as wel as structural reqttirementand in some structurea , the need for making watertight joint is primary cosideration.